2018
DOI: 10.1038/s41467-018-04210-y
|View full text |Cite
|
Sign up to set email alerts
|

Precisely timed inhibition facilitates action potential firing for spatial coding in the auditory brainstem

Abstract: The integration of excitatory and inhibitory synaptic inputs is fundamental to neuronal processing. In the mammalian auditory brainstem, neurons compare excitatory and inhibitory inputs from the ipsilateral and contralateral ear, respectively, for sound localization. However, the temporal precision and functional roles of inhibition in this integration process are unclear. Here, we demonstrate by in vivo recordings from the lateral superior olive (LSO) that inhibition controls spiking with microsecond precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 64 publications
3
66
2
2
Order By: Relevance
“…In vivo and at physiological temperatures, the inhibitory window is probably shorter and falls in the sub‐millisecond range, as suggested by recent in vivo recordings in gerbils (Beiderbeck et al . ). We showed with voltage clamp measurements that the inhibitory conductance needed to be ∼2‐fold larger than the excitatory one to guarantee suppression of AP firing driven by bushy cell inputs (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In vivo and at physiological temperatures, the inhibitory window is probably shorter and falls in the sub‐millisecond range, as suggested by recent in vivo recordings in gerbils (Beiderbeck et al . ). We showed with voltage clamp measurements that the inhibitory conductance needed to be ∼2‐fold larger than the excitatory one to guarantee suppression of AP firing driven by bushy cell inputs (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…) and also with recent in vivo findings (Beiderbeck et al . ). In our simulations with a simple integrate‐and‐fire model, the difference between large constant unitary ISPCs and the more realistically large unitary IPSCs with variable amplitudes was not large (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…) is involved in sound source localization by detecting interaural level differences (ILDs) upon precise integration of cochlear nucleus‐mediated excitation and MNTB‐mediated inhibition (Tollin, ; Yin & Kuwada, ; Beiderbeck et al . ; Friauf et al . ).…”
Section: Introductionmentioning
confidence: 96%
“…In the mammalian auditory brainstem, a glycinergic projection from the MNTB to the LSO (Fischer et al 2019) is involved in sound source localization by detecting interaural level differences (ILDs) upon precise integration of cochlear nucleus-mediated excitation and MNTB-mediated inhibition (Tollin, 2003;Yin & Kuwada, 2010;Beiderbeck et al 2018;Friauf et al 2019). The MNTB-LSO circuit is functionally refined during the first two postnatal weeks in rats and mice (Kim & Kandler, 2003;Hirtz et al 2012;Clause et al 2014), and refinement coincides with the presence of spontaneous prehearing activity.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility seems particularly plausible given that immunohistochemical studies have shown that the tonotopic organization is degraded [15,16] and that stimulation-induced molecular, morphological, and electrophysiolological plasticity is altered in neonatally deafened rats compared to CI-stimulated rats with normal auditory development [15][16][17][18][19]. Furthermore, it has been shown that early acoustic experience shapes ITD tuning curves in key brainstem nuclei of gerbils [20], probably by shaping the precise timing of inhibitory inputs into superior olivary nuclei [20,21]. However, it is also possible that the unstimulated auditory pathway may retain the ability to encode ITDs during a period of early deafness, and may only lose it as a result of maladaptive plasticity after a period of CI stimulation which conveys no useful ITD information.…”
mentioning
confidence: 99%